E-ABRM: enhanced ABRM routing protocol for MSNs with multiple mobile sinks. (2018) - Soliman, Maged S.; Fahmy, Hossam M.A.
The recent technological advances in the field of wireless sensor networks (WSNs) have expanded the range of WSN applications. In some of these applications, sensor nodes are mobile rather than static. Also, the recent advances in personal digital assistants (PDAs) allow the existence of multiple mobile sinks to collect the sensors data. These characteristics require the design of new routing protocols to meet the existence of mobile sensors and multiple mobile sinks while taking into consideration the limited resources for sensor nodes especially the energy. In-network aggregation is one of the important techniques used to save power consumption by aggregating the data on sensor nodes before transmitting towards the sinks and hence reduce the number of transmissions required. ABRM, as previously proposed, is an aggregation based routing protocol for mobile sensor networks (MSNs) with multiple mobile sinks. This paper proposes enhanced ABRM (E-ABRM) to improve the aggregation results and reduce the routing overhead and power consumption. E-ABRM is compared to ABRM and CCBR through mathematical analysis and simulation results. The comparisons show that E-ABRM reduces aggregation error, routing overhead, and energy consumption.